Screening of Endophytic Bacteria Isolated from Mimosa pudica in Bali Island - Dewa Gede Wiryangga Selangga; Listihani (SEAS (Sustainable Environment Agricultural Science), 2021)
This study aims to determine the screening of endophytic bacteria isolatd from Mimosa pudica in Bali Island. This research was conducted from September 2020 to January 2021 at the Plant Disease Laboratory, Faculty of Agriculture, Udayana University, Denpasar. Isolation of endophytic bacteria was carried out by taking a sample of the root of the shy daughter plant which was then washed and dried on a tissue.. Hypersensitivity test followed Klement and Goodman (1967) by growing bacteria in a petri dish containing 100% TSA and NA.Tests were carried out by growing endophytic bacteria in 100% NA and TSA media. Isolation of the roots of the Mimusa pudica plant resulted in 43 isolates. The resulting isolates then passed the hypersensitive test so that 27 isolates were selected. A total of 27 isolates were then tested for hemolysis on blood agar. The final results obtained were 12 endophytic bacterial isolates which were then used in the next practicum. The results showed that the endophytic bacterial isolates were not able to inhibit the fusarium sp. and Phytophthora sp., when using the inhibition percentage formula. This is because the average diameter of the pathogenic fungi colonies in the control treatment (R1) with the average diameter of the pathogenic fungi colonies in the endophytic treatment (R2) has the same size, so that when calculated by the percentage inhibition formula it results in the number 0 which means no. there is a zone of inhibition.